A new methodology to assess the solubility of fatty acids: Impact of food emulsifiers - Naso, Julieta Natalia (2021)
In food formulations, lipids are normally incorporated as emulsions stabilized by different types of emulsifiers. The emulsifiers can affect fatty acid (FA) solubilization as they can interact with FA. The main purpose of the present work is the development of a methodology to evaluate the FA solubilization in an aqueous medium in the absence and presence of exogenous emulsifiers. To this end, a combination of turbidimetry, oiling off and dynamic light scattering (DLS) was used. The FA solubility, as well as its supramolecular assemblies, were determined by analyzing the changes in the turbidity profile and the corresponding size of particles obtained by DLS. Oleic acid (OA) was used as a model FA and a simulated intestinal fluid (SIF) as the aqueous phase. Emulsifiers of low (Tween 80) and high (protein and polysaccharide) molecular weight were tested. Tween 80 was the only emulsifier that improved OA solubilization, whereas the macromolecules only affected the supramolecular structure that OA adopted, being the structure of these assemblies governed by the emulsifier nature.